Effect of Product Quality, Advertisement, and Brand Image on Purchase Decision Mediated By Customer Value of Louis Vuitton at Jabodetabek - Zoel Hutabarat (Universitas Muhammadiyah Jakarta, 2022)
This study was conducted to determine the effect of product quality, advertising, brand image, and customer value on Louis Vuitton purchasing decisions in the Greater Jakarta area. To achieve the research objectives, the researcher used quantitative research which was applied to 168 Louis Vuitton consumers in Greater Jakarta. Researchers tested validity and reliability and processed respondent data using the SmartPLS ver 3 application. The results showed that there was a positive and significant influence of advertising and customer value on purchasing decisions. But product quality and brand image have no positive and significant effect and the results also show no significant effect between product quality and customer value.